2017
DOI: 10.1039/c7ra02291c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic metal–organic frameworks as scaffolds for spatial co-location and positional assembly of multi-enzyme systems enabling enhanced cascade biocatalysis

Abstract: Magnetic multi-enzyme nanosystems have been prepared via co-precipitation of enzymes and metalorganic framework HKUST-1 precursors in the presence of magnetic Fe 3 O 4 nanoparticles. The spatial co-localization of two enzymes was achieved using a layer-by-layer positional assembly strategy.Glucose oxidase (GOx) and horseradish peroxidase (HRP) were used as the model enzymes for cascade biocatalysis. By controlling the spatial positions of enzymes, three bienzyme nanosystems GOx@HRP@HKUST-1@Fe 3 O 4 , GOx-HRP@H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 54 publications
3
66
0
Order By: Relevance
“…Specifically, we varied the mass ratio of CelDZ1, bgl, GOx and HRP from 1:1:1:1 to 1:1:1:3, respectively. It was indicated that the use of excess HRP concentration during the immobilization process, enhanced the final step of the studied cascade process, a result that is in accordance with other studies that reported that the increase in the initial amount of HRP is essential in the development of robust bi-enzymatic systems comprising of GOx and HRP [28,29]. Glutaraldehyde, acting as a bifunctional cross-linker, reacts with the amino groups of both the enzymes and the MNPs, directly affecting enzyme loading, activity recovery and operational stability of the prepared nanobiocatalyst [30].…”
Section: Preparation Of the Magnetic Four-enzyme Nanobiocatalystsupporting
confidence: 87%
“…Specifically, we varied the mass ratio of CelDZ1, bgl, GOx and HRP from 1:1:1:1 to 1:1:1:3, respectively. It was indicated that the use of excess HRP concentration during the immobilization process, enhanced the final step of the studied cascade process, a result that is in accordance with other studies that reported that the increase in the initial amount of HRP is essential in the development of robust bi-enzymatic systems comprising of GOx and HRP [28,29]. Glutaraldehyde, acting as a bifunctional cross-linker, reacts with the amino groups of both the enzymes and the MNPs, directly affecting enzyme loading, activity recovery and operational stability of the prepared nanobiocatalyst [30].…”
Section: Preparation Of the Magnetic Four-enzyme Nanobiocatalystsupporting
confidence: 87%
“…[34,35,48] Moreover, by selecting the appropriate MOF materials for immobilization, multi-enzyme cascade reactions can be accurately controlled by the spatially positioned and orientated enzymes in nanoscale-precision. [39,49,50] In addition, to endow multi-enzyme catalysis with the smart and stimuli-responsive property, compartmentalization of enzymes sometimes is required to provide a separated space for different enzymes, which is helpful to regulate enzymes and enhance their whole catalytic performance. [41,55,56] More excitingly, with the merits of compartmentalization strategy and communication capability of MOFs, some chemically incompatible enzymes (e. g. protease and glucose oxidase) can be coupled together to function cooperatively for chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, with satisfying advantages, multi-enzyme cascade reactions in MOFs have been exploited in several field. For example, with multi-enzyme encapsulated in MOFs, the multi-enzyme@MOF systems highlight new possibilities in biosensors, which enable a series of biomarkers detection such as glucose, [34,35,42,49,53] cholesterol, [37] uric acid, [42] lactose, [53] and so on. Furthermore, due to the high enzyme loading capacity, biodegradability, and high biocompatibility in vitro and in vivo, multi-enzyme@MOF systems have also shown considerable promise in catalytic nanomedicine applications, such as glucose oxidase (GOx) and horseradish peroxidase (HRP) or chloroperoxidase (CPO) co-encapsulated in MOFs induced high toxic reactive oxygen species (ROS) generation for tumor cell therapy, [44,45] and GOx and catalase co-immobilized within MOFs enabled smart drug delivery with negligible cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The seed crystal method has also been successfully applied to the preparation of Fe 3 O 4 @HKUST‐1 . Fe 3 O 4 @Cu 2+ @H 3 BTC was obtained by dispersing the citric acid‐coated Fe 3 O 4 nanoparticles into copper(II) acetate and H 3 BTC respectively, and then under hydrothermal conditions as a seed crystal to prepared Fe 3 O 4 @HKUST‐1.…”
Section: Preparation Magnetic Framework Compositesmentioning
confidence: 99%